An introduction to Medieval English literature : - Baldwin, Anna P. (Palgrave;, 2016)
"This book provides an informative, critical and concise introduction to the literature of the fourteenth and fifteenth centuries, contextualising the literature and introducing the pre-eminent authors of the period. "--